Absolutism in Renaissance Milan : plenitude of power under the Visconti and the Sforza, 1329-1535 - Black, Jane, 1945- (Oxford University Press, 2009)
Absolutism in Renaissance Milan shows how authority above the law, once the preserve of pope and emperor, was claimed by the ruling Milanese dynasties, the Visconti and the Sforza, and why this privilege was finally abandoned by Francesco II Sforza (d. 1535), the last duke. As new rulers, the Visconti and the Sforza had had to impose their regime by rewarding supporters at the expense of opponents. That process required absolute power, also known as 'plenitude of power', meaning the capacity to overrule even fundamental laws and rights, including titles to property. The basis for such power re.